Frequency and Systemic Associations of Focal Low-Trabeculation/Low-Density Intramedullary Jawbone Findings: A Retrospective CBCT Study - Marzena Dominiak; Wojciech Niemczyk; Artur Pitułaj; Witold Świenc; Sebastian Dominiak; Konstanty Sławecki; Łucja Janek; Jacek Matys (Journal of Clinical Medicine, 2026)
Background: This exploratory study assessed the frequency of study-defined focal low-trabeculation/low-density intramedullary findings (FLDIFs) in a selected clinical cohort referred for cone-beam computed tomography (CBCT) and examined their associations with demographic, systemic, and radiographic variables. CBCT depicts mineralized trabecular architecture and relative attenuation but cannot directly demonstrate marrow fat or establish osteonecrosis; FDOJ/MFI were therefore considered only possible interpretations rather than imaging diagnoses. Methods: A single-center retrospective analysis included 1000 adults whose CBCT examinations met the study image-quality and anatomical-coverage requirements. FLDIF was defined as a descriptive radiological phenotype and was not considered a diagnosis of fatty degenerative osteonecrosis of the jaw (FDOJ), marrow fatty infiltration (MFI), or another specific disorder. Patients were classified as positive when at least one study-defined finding was present; one largest index finding per positive patient was used for finding-level analyses. Results: FLDIFs were identified in 452/1000 patients (45.2%; 95% CI: 42.1–48.3%) within this CBCT-referred cohort. Age was associated with finding presence in the multivariable model (OR 1.015 per year, 95% CI: 1.006–1.025; p = 0.001). Diabetes mellitus also showed an adjusted association (OR 1.647, 95% CI: 1.022–2.686; p = 0.042), which should be regarded as exploratory because of residual confounding and retrospective disease ascertainment. Panoramic radiographs were available for all 452 index findings; 180 (39.8%) were judged visible and 272 (60.2%) not visible. Visible index findings were larger (median 9.2 vs. 8.1 mm; pFDR = 0.003; |rank-biserial r| = 0.19), whereas the relative CBCT gray-scale comparison was not significant after FDR correction. Most index findings (412/452, 91.2%) were located in the mandibular retromolar regions. Conclusions: The 45.2% value represents the frequency of a study-defined, nonspecific radiological phenotype within a selected CBCT-referred cohort and should not be interpreted as population prevalence or as the prevalence of histopathologically confirmed FDOJ/MFI. The findings are hypothesis-generating; they do not establish a screening indication for CBCT based on age or diabetes. The biological and clinical significance of the imaging phenotype remains uncertain and requires external validation in independent cohorts and, when clinically indicated, histopathological or complementary imaging correlation.